Determinants of Capital Adequacy Ratio in KBMI 4 Banks: Evidence from Profitability and Liability Structure in Indonesia (2021–2025) - Virza Utama Alamsyah (Sanskara Manajemen Dan Bisnis, 2026)
This study examines the determinants of the Capital Adequacy Ratio (CAR) and liability composition among the four KBMI 4 banks listed on the Indonesia Stock Exchange (IDX), namely BBCA, BBRI, BMRI, and BBNI, over the quarterly period from 2021 to 2025. The analysis is based on 80 bank-quarter observations extracted from publicly available financial statements and verified using bank-level individual data reported in millions of Indonesian Rupiah. The primary dependent variable is the Capital Adequacy Ratio (CAR), while the independent variables include Return on Assets (ROA), Gross Non-Performing Loans (NPL), Loan-to-Deposit Ratio (LDR), bank size, and liability composition proxied by the Deposit-to-Liability Ratio (DLR). Panel data regression with bank fixed effects and HC1 robust standard errors is employed to estimate the relationships. The results indicate that ROA and liability composition have a positive and statistically significant effect on CAR, whereas NPL, LDR, and bank size are not statistically significant in the baseline model. Robustness tests using winsorization and time fixed effects confirm that profitability and a funding structure dominated by customer deposits remain the most consistent determinants of CAR among KBMI 4 banks. This study contributes to the banking literature by demonstrating that capital adequacy in large commercial banks should be interpreted as an indicator of capital quality supported by sustainable profitability and stable funding, rather than merely as a measure of regulatory compliance. For investors, the findings suggest that CAR should be evaluated jointly with ROA, deposit-based funding structure, credit quality, and risk-weighted asset expansion capacity when assessing the fundamental performance and financial resilience of banking stocks.